An empirical study of benchmarking evaluation using MCDM in service industries. Issue 2 (6th February 2017) - Singh, Bhupender; Grover, Sandeep; Singh, Vikram
Abstract : Purpose: The purpose of this paper is to generate awareness of contributions made by benchmarking toward building performance of Indian service industries in globally market. Ranking of Benchmarking is done on the basis of their application which give confidence for the managers to adopt in their Industries so that they may become best in their field. Design/methodology/approach: Methodology consists of three phase: define, phase include definitions, factors of benchmarking as literature outcomes, questionnaire survey and outcome of survey. In the second phase, analysis of collected data and applications of multi-criteria decision-making approaches [technique for order preference by similarity to ideal solution (TOPSIS) and analytical network process (ANP)] are used. The last phase includes comparison of results which gives validation in similarities of ranking obtained. Findings: The study identifies seven different benchmarking techniques used for service industries. Using TOPSIS and ANP approaches shows similarity that external benchmarking, performance benchmarking and internal benchmarking are the first three ranks that give basis for several critical success factors s, namely, planning, reliability, standardization, time behavior, usability, etc., as part of benchmarking using in service industries. Research limitations/implications: The limitation is the assumptions made by multi-criteria decision-making approaches which may effect the analysis of the study as these are taken theoretically. Originality/value: This study is a first attempt to find similarities in both techniques while comparing benchmarking in Indian service industries.